Поняття та особливості нагляду (контролю) за якістю надання освітніх послуг закладами вищої освіти зі специфічними умовами навчання - Яценко, Ф. П.; Yatsenko, F. P. (Наше право. - 2021. - № 3. - С. 212-217, 2021)
У статті, спираючись на аналіз наукових поглядів вчених, розкрито сутність та зміст понять «нагляд» та «контроль». Розкрито теоретичні підходи щодо тлумачення поняття «якість освіти». Запропоновано авторське визначення «нагляду (контролю) за якістю надання освітніх послуг закладами вищої освіти зі специфічними умовами навчання», а також виділено його ключові ознаки.

It is noted that the specificity of supervision (control) over the quality of the provision of educational services by institutions of higher education with specific learning conditions is due, first of all, to its purpose, which consists in establishing compliance between the level of organization, provision and implementation of the educational process, the requirements and standards put forward to future employees of various central executive bodies subordinate to the Ministry of Internal Affairs of Ukraine. It has been proven that the supervision (control) of the quality of the provision of educational services by institutions of higher education with specific conditions of study is most expediently interpreted as the activity of specially authorized entities regulated by the norms of current legislation, which is aimed at establishing the compliance of the educational activities of these higher education institutions with the established standards of higher education, as well as normatively - legal requirements of the central executive authorities regarding the level of training of specialists with specific knowledge, abilities and skills to perform the tasks and functions of these institutions. The most characteristic features of supervision (control) of supervision (control) over the quality of provision of educational services by institutions of higher education with specific conditions of study include: firstly, it has a dual nature, because, on the one hand, it is aimed at checking the quality of provision of educational services of higher education institutions with specific conditions of study, as entities that carry out general training of higher education seekers, and on the other hand, as a special institution that trains specialists for further service in the system of the Ministry of Internal Affairs of Ukraine; secondly, when conducting it, it is necessary to observe the principles of legality, systematicity, objectivity, comprehensiveness, openness, and transparency. At the same time, the legal requirements regarding the observance of state secrets related to the specifics of the activities of such educational institutions should be taken into account; thirdly, based on the results of supervision (control), decisions are made regarding the conformity or non-conformity of educational services with the requirements and standards defined by legislation, as a result of which management decisions are made. At the same time, in case of detection of offenses, officials of higher education institutions with specific study conditions bear increased responsibility according to the current legislation of Ukraine.

В статье, опираясь на анализ научных взглядов ученых, раскрыта сущность и содержание понятий "надзор" и "контроль". Раскрыты теоретические подходы к толкованию понятия «качество образования». Предложено авторское определение надзора (контроля) за качеством предоставления образовательных услуг заведениями высшего образования со специфическими условиями обучения», а также выделены его ключевые признаки.
Keywords: нагляд; контроль; освітні послуги; якість освіти; заклади вищої освіти зі специфічними умовами навчання; supervision; control; educational services; quality of education; institutions of higher education with specific study conditions; надзор; образовательные услуги; качество образования; заведения высшего образования со специфическими условиями обучения